Lexical cohesion in the commercial advertisements of five Korean magazines - Serly Rachmawati; Didi Sukyadi; Didin Samsudin (Journal of Korean Applied Linguistics, 2021)
Lexical cohesion is considered an essential element in understanding a discourse. However, the forms of lexical cohesion in commercial Korean advertisements are still under-explored. This study aims to examine 1) the forms of lexical cohesion found in the commercial advertisements of five Korean-language magazines; 2) the most dominant form of lexical cohesion in the advertisements; and 3) the functions of using the lexical cohesion forms in the advertisements. This study employed a descriptive qualitative method. The research data were collected through careful comprehension and note-taking technique. The results demonstrated that five forms of lexical cohesion were found in the advertisements: repetition, synonym, antonym, hyponym, and collocation. Repetition was the most frequently occurred lexical cohesion form (n=30 times). Most of the commercial advertisements analyzed employed repetition to emphasize the advantages of the advertised product or service. This results indicate that the analyzed commercial advertisements are considerably cohesive. It can be seen from the use of lexical cohesion forms that makes the discourse of commercial advertising holistic and intelligible.